2021
DOI: 10.1186/s12995-021-00336-w
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial demands and resources for working time organization in GP practices. Results from a team-based ethnographic study in Germany

Abstract: Background General practitioners (GPs) are challenged, e.g. by long working hours, and as employers they are responsible for the creation of working conditions that prevent work-related psychosocial risks. Leadership behaviour plays an important role within the working conditions of employees, thus we focused on two research questions: To what extent and how do GPs fulfil their role as entrepreneurs and leaders responsible for occupational safety and health of the team members in the organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Help or translation is often requested by patients or physicians. The interviewed MA felt integrated into the family practice setting and reported no additional stress or resources emerging from the additional tasks they were assigned due to their migration background Communication and interaction with patients Language connection [ 55 ] Preiser et al 2021 19 w Qualitative, cross-sectional; participant observation, semi-structured interviews and focus group discussions To answer how GP fulfill their role as entrepreneurs and leaders responsible for the occupational safety of their employees regarding the organization of working time, and what psychosocial demands and resources result from the way how working time for practice teams is organized Work content and task “Unplannable” events considered part of the daily routine during consultation hours and lead to perceived psychological stress for GP and the practice team. MA expressed satisfaction with the flexibility of different working time models and the GP’s overall willingness to adjust working time models and hours to their needs.…”
Section: Resultsmentioning
confidence: 99%
“…Help or translation is often requested by patients or physicians. The interviewed MA felt integrated into the family practice setting and reported no additional stress or resources emerging from the additional tasks they were assigned due to their migration background Communication and interaction with patients Language connection [ 55 ] Preiser et al 2021 19 w Qualitative, cross-sectional; participant observation, semi-structured interviews and focus group discussions To answer how GP fulfill their role as entrepreneurs and leaders responsible for the occupational safety of their employees regarding the organization of working time, and what psychosocial demands and resources result from the way how working time for practice teams is organized Work content and task “Unplannable” events considered part of the daily routine during consultation hours and lead to perceived psychological stress for GP and the practice team. MA expressed satisfaction with the flexibility of different working time models and the GP’s overall willingness to adjust working time models and hours to their needs.…”
Section: Resultsmentioning
confidence: 99%
“…The potential for primary care transformation and better health system performance remains unresearched and focuses mainly on operational benefits and 24-hour patient access [ 13 ]. Our previous work showed that work-related demands in general practice are already high [ 60 , 61 ], indicating that new technologies need to fit the needs and routines of HCPs to find acceptance [ 62 ]. Real-life implications of SCs, especially with regard to the changes in the daily working routines of GPs and more generally HCPs in primary care, are not well understood [ 47 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…We planned semi-structured interviews with company owners and executive managers as well as focus group discussions with employees from different enterprises in the health and service sector to identify work-related psychosocial demands relevant from the company owner/manager as well as the employee perspective. Initially, we planned to conduct a participatory observation of team meetings to triangulate different methods to continue our recent study addressing psychosocial demands in general practices [ 25 , 26 ]. During the recruitment process, it became evident that none of the included companies conducted regular team meetings.…”
Section: Methodsmentioning
confidence: 99%
“…Since we wanted to encourage discussion on these topics, the questions of the interview guide were put in a narrative-generating way and we avoided yes/no questions. The interview guide was previously tested and large parts of it were successfully applied in a study among managers and employees in general practices as another SME setting [ 24 – 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation